Trait specific germplasm of oilseed crops Status of registration - Sharma, H. K.; Sharma, Pankaj; Singh, V. V.; Meena, H. S.; Priyamedha, Priyamedha; Meena, B. L.; Kak, Anjali; Rai, P. K. (Indian Farming, 2021)
International Undertaking on Plant Genetic Resources (FAO, 1983) defines PGR as the reproductive or vegetative propagating material of modern cultivars, obsolete cultivars, landraces, wild and weed species, near relatives of cultivated varieties and special genetic stocks (including elite and current breeder’s lines and mutants). PGR, according to the Convention for Biological Diversity, are any living material of present and potential value for humans. In present time genomic resources including genes, DNA fragments and RNA are also being conserved in gene banks.